NUCLEAR ENERGY IMPLEMENTATION IN TRANSITION PHASE TOWARD NET ZERO EMISSION PROGRAM - Permana, Sidik
A roadmap of zero net CO2 emission program by 2060 has been announced to fulfil the estimated national energy demand and adopting net zero emission program that shows an ambitious program of future green energy in Indonesia. It shows that the policy want to strengthen the green energy resources which are based on the new and renewable energy resources (NRE). The NRE contributions will be dominant and in the same time fossil energy will be gradually decreasing before 2060. Utilization of nuclear energy for energy applications, including for nuclear power plants (NPP) and energy co-generation applications, including water desalination, hydrogen production, for coal gasification and liquefaction and enhanced oil recovery (EOR) applications which can be used for NZE program. The objective of this study is to show the contribution of nuclear energy for the implementation of Net Zero Emission (NZE) Program in Indonesia. Several adopted methodology are used such as the method for system thinking which is based on rich pictures approach, causal loop diagram method (CLD) and competitive advantages method. There are several methods to collect the data such as Literacy on document review, discussion in seminar or focus group discussion as well as a discussion with source person in BRIN (National Research and Innovation Agency), University, DEN or national energy council, Ministry of energy and mineral resources MEMR and BAPETEN or nuclear regulatory agency in Indonesia as well as non-government organisation of HIMNI as well document review process. It shows the present status of NPP utilization in the world and technology advancement on NPP program, analysis on Competitive advantages of Nuclear energy, the evaluation based on net zero emission program focused on NPP program contribution, analysis on Economy competitiveness of NPP by adopting levelized cost of electricity (LCOE) methodology, evaluation based on mapping strategy for NPP power capacity scale for the electricity demand in Indonesia, analysis and mapping for NPP utilization for special purposes of special economy or industrial zone and de-dieselization programs which are some of the national project program for electrification for remote area and isolated zone have been evaluated. In NZE program, Nuclear energy as a part of new and renewable energy contributes to the national energy mix starting from 2040 for NPP contribution. Nuclear program should be implemented from planning, preparation and investment as well as preparing the human resources and some other infrastructure for nuclear energy program. It can be used for small energy demand, remote area or island, specific industrial zone or industrial complex as well as for de-dieselization program. As part of recommendation, LCOE analysis of NPP has been conducted and it shows that LCOE of NPP in Europe are about 42 USD/MWh up to 102 USD/MWh, and LCOE in USA, it can be seen at around 71. Similar analysis has been done for LCOE in Asia which shows that LCOE in Asia are about 50 USD/MWh up to 87 USD/MWh. LCOE for SMR type is estimated to have in average value of 60 USD/MWh and the maximum value of LCOE is about 90 USD/MWh. It can be used for small energy demand, remote area or island, specific industrial zone or industrial complex. The utilization of NPP analysis for special zone has been conducted such for industrial zone. Based on 26 industrial zones, it has the electricity demand range 10 MWe up to 1000 MWe power range. From the list the zones for another industrial zone non RPJMN require the electricity demand from 15 MWe up to 2,4 GWe depends on the area. The use of NPP for industrial zone will be depending on the electricity scale or demand which is in the range of 10 to 2,4 GWe. The distribution of de-dieselization program very scatter in all island in Indonesia and those area has electricity demand depending on the area for the electricity demand range from 0,6 MWe up to 550 MWe. The potential utilization of NPP for de-dieselization program will be depending on the electricity scale or demand which is in the range of 0,6 MWe up to 550 MWe electricity demand. As mentioned before that nuclear energy contribute to 18 % which is equal to 324 TWh in 2060 as a part of NZE program. It shows Java Island will have about 214 TWh electricity from nuclear energy, while Sumatra island will use 64 of Nuclear energy and the other island Kalimantan, Sulawesi and the rest will use 14,4 TWh, 16,7 TWh and 14,2 TWh, respectively. If the electricity demand in TWh is transform into the power capacity of power plant, it will be equal to about 46 GWe power capacity of NPP. The estimation of installed capacity for each island is shown that Java island requires install capacity of NPP about 30,3 GWe, while sumantra island required 9 GWe and other island requires 2-2,4 GWe install capacity. RE contribution is assumed contribute 100% utilization factor (430 GWe equal 1159 TWh), fossil energy and nuclear energy contribute to fill the gap. When 100% NRE contribution, renewable and nuclear energy become 100%, therefore nuclear energy contribution become 641 TWh to fulfil the gap of NZE target 1800 TWh. The nuclear energy is estimated to be in operation and contributes to the national energy mix starting between 2035-2040 based on several scenarios and NPP should be implemented as a program for NZE starting from 2023-2024 to reach the operation early 2030s. By implementing nuclear energy, it requires a NEPIO or Nuclear Energy Programme Implementing Organization which has a duty to implement the nuclear energy program from planning, preparation and investment as well as preparing the human resources and some other infrastructure for nuclear energy program.